Diplomasi Publik Organisasi Nonpemerintah dalam Membangun Citra Indonesia: Studi Kegiatan 'Koalisi untuk Kebebasan Informasi' - Asep Saefudin (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
The research is aimed to find out the “Coalition for Freedom of Information” activity, or Coalition, that can be categorized public diplomacy, its relationship with implementing thegovernment as the requirement to realize the good governance, and to get to know the relationship between good governance and the image building of Indonesia. The principles of public relations are used as the approach in analyzing the phenomenon of public diplomacy used by Coalition. This research was conducted by using the qualitative approach through constructivist paradigm toward the Coalition attitude in applying the public diplomacy. This research used both the key and supporting informa collecting was conducted by interview, observation, participation, and documentary study about the Coalition activity as well as the delphi technique. The data analysis was carried out as long as the research went on through the intersubjective commitment to focus being researched. The research gained some findings which involved: (a) The “Coalition for Freedom of Information” activity in public diplomacy can be done by the public relations approach using some activity categories, (b) The “Coalition for freedom of information” performance is focused on the efforts to uphold the law concerning freedom of access to public information in supporting the realization of good governance, (c) The public diplomacy activity applied by the Coalition through its advocacy was considered successful which can be seen by the local government rules concerning the implementation of participative and transparent government, (d) The model with the integrated public diplomacy potency and the synergy between the state actor and the non-state actor possessing their own structural authority and legality in the information service system for all public elements can build the positive image of Indonesia.